Co-expressing GroEL–GroES, Ssa1–Sis1 and Bip–PDI chaperones for enhanced intracellular production and partial-wall breaking improved stability of porcine growth hormone - Jinbo Deng; Jiaoqing Li; Miaopeng Ma; Peijing Zhao; Feiping Ming; Zhipeng Lu; Juqing Shi; Qin Fan; Qianyi Liang; Junhao Jia; Jiayi Li; Shuxia Zhang; et al. (Microbial Cell Factories, 2020)
Abstract Porcine growth hormone (pGH) is a class of peptide hormones secreted from the pituitary gland, which can significantly improve growth and feed utilization of pigs. However, it is unstable and volatile in vitro. It needs to be encapsulated in liposomes when feeding livestock, whose high cost greatly limits its application in pig industry. Therefore we attempted to express pGH as intracellular soluble protein in Pichia pastoris and feed these yeasts with partial wall-breaking for swine, which could release directly pGH in intestine tract in case of being degraded in intestinal tract with low cost. In order to improve the intracellular soluble expression of pGH protein in Pichia pastoris and stability in vitro, we optimized the pGH gene, and screened molecular chaperones from E. coli and Pichia pastoris respectively for co-expressing with pGH. In addition, we had also explored conditions of mechanical crushing and fermentation. The results showed that the expression of intracellular soluble pGH protein was significantly increased after gene optimized and co-expressed with Ssa1–Sis1 chaperone from Pichia pastoris. Meanwhile, the optimal conditions of partial wall-breaking and fermentation of Pichia pastoris were confirmed, the data showed that the intracellular expression of the optimized pGH protein co-expressed with Ssa1–Sis1 could reach 340 mg/L with optimal conditions of partial wall-breaking and fermentation. Animal experiments verified that the optimized pGH protein co-expression with Ssa1–Sis1 had the best promoting effects on the growth of piglets. Our study demonstrated that Ssa1–Sis1 could enhance the intracellular soluble expression of pGH protein in Pichia pastoris and that partial wall-breaking of yeast could prevent pGH from degradation in vitro, release targetedly in the intestine and play its biological function effectively. Our study could provide a new idea to cut the cost effectively, establishing a theoretical basis for the clinic application of unstable substances in vitro.